Novel bimodal radiofrequency cavity enabling independent operation and effective higher-order mode damping for high-brightness particle beams - Junyu Zhu; Xiao Li; Jiebing Yu; Zhijun Lu; Xuerui Hao; Bin Wu; Chunlin Zhang; Wei Long; Yang Liu; Shengyi Chen; Shenghua Liu; Jian Wu; et al. (Physical Review Accelerators and Beams, 2025)
Developing multifrequency acceleration systems is crucial for optimizing beam dynamics in high-brightness particle beams, particularly for minimizing energy spread, manipulating bunch length, and facilitating beam bunching. This paper introduces a novel bimodal radio frequency (rf) cavity design that integrates both fundamental and harmonic modes within a single structure, offering enhanced spatial efficiency and improved operational flexibility for multifrequency rf systems. Unlike traditional designs, our cavity enables independent and simultaneous operation of each mode, along with effective suppression of higher-order modes (HOMs), which is critical for high-current beam stability. This breakthrough addresses significant challenges in bimodal cavity technology, such as intermode tuning coupling, rf-driving coupling, and effective HOM damping, providing essential solutions for high-current beam applications. Our work opens new research avenues in advanced rf cavity design, with significant implications for the future of high-brightness beam technologies, including advanced accelerator designs and improved beam quality.